In vitro CONTROL OF FISH HELMINTH PARASITE, Euclinostomum heterostomum BY FLAVONOID-RICH EXTRACTS OF Mangifera indica - KUNDU, IVY; RAHMAN, MD. MAHAFUJ; ROY, SNEHA; KHATUN, YASHMIN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The study was conducted to determine anthelminthic activity of mango plant (Mangifera indica) known widely for its medicinal value. Alcoholic extracts of leaves of mango plant was tested as a therapeutic agent for controlling Euclinostomum heterostomum, trematode parasite in fish by ‘in vitro’ method. Qualitative and quantitative estimation of the ethyl acetate extract showed higher flavonoid content compared to ethanol and chloroform extracts. The ethyl acetate extract was found to be effective in killing parasites significantly (LC50 value 8.2016 mg/l) which clearly demonstrates the anthelminthic activity of mango leaves. Acute toxicity tests of ethyl acetate extracts on host animals (Channa punctata) showed the lethal concentration (LC50) value of 194.98 mg/l, thus a considerable lower effective working solution can be used for application for control of parasites without causing damage to host animals. On the basis of above study, it can be concluded that the mango leaves can be used as an alternative to synthetic drugs applied indiscriminately to control helminth parasites which has resulted in serious health concern.